Enhanced plasmid-mediated bioaugmentation of RDX-contaminated matrices in column studies using donor strain Gordonia sp. KTR9. (1st October 2019) - Jung, Carina M; Carr, Matthew; Blakeney, G Alon; Indest, Karl J
Abstract: Horizontal gene transfer (HGT) is the lateral movement of genetic material between organisms. The RDX explosive-degrading bacterium Gordonia sp. KTR9 has been shown previously to transfer the pGKT2 plasmid containing the RDX degradative genes ( xplAB ) by HGT. Overall, fitness costs to the transconjugants to maintain pGKT2 was determined through growth and survivability assessments. Rhodococcus jostii RHA1 transconjugants demonstrated a fitness cost while other strains showed minimal cost. Biogeochemical parameters that stimulate HGT of pGKT2 were evaluated in soil slurry mating experiments and the absence of nitrogen was found to increase HGT events three orders of magnitude. Experiments evaluating RDX degradation in flow-through soil columns containing mating pairs showed 20% greater degradation than columns with only the donor KTR9 strain. Understanding the factors governing HGT will benefit bioaugmentation efforts where beneficial bacteria with transferrable traits could be used to more efficiently degrade contaminants through gene transfer to native populations.